Age-related olfactory decline is associated with the BDNF val66met polymorphism: evidence from a population-based study - Hedner, Margareta; Nilsson, Lars_Göran; Olofsson, Jonas K.; Bergman, Olle; Eriksson, Elias; Nyberg, Lars; Larsson, Maria (Frontiers in Aging Neuroscience, 2010)
The present study investigates the effect of the brain-derived neurotrophic factor (BDNF) val66met polymorphism on change in olfactory function in a large scale, longitudinal population-based sample (n=836). The subjects were tested on a 13 item force-choice odor identification test on two test occasions over a 5-year-interval. Sex, education, health-related factors, and semantic ability were controlled for in the statistical analyses. Results showed an interaction effect of age and BDNF val66met on olfactory change, such that the magnitude of olfactory decline in the older age cohort (70-90 years old at baseline) was larger for the val homozygote carriers than for the met carriers. The older met carriers did not display larger age-related decline in olfactory function compared to the younger group. The BDNF val66met polymorphism did not affect the rate of decline in the younger age cohort (45-65 years). The findings are discussed in the light of the proposed roles of BDNF in neural development and maintenance.